Democratic parenting style and college student independence: Examining the role of socioeconomic status - Amalia Wada Sabillah; Chamilul Hikam Al Karim (Jurnal Psikologi Terapan dan Pendidikan, 2026)
Student independence is an important psychosocial developmental aspect that supports academic adjustment and preparation for adult life. However, factors associated with student independence require further empirical investigation, particularly in the Indonesian context. This study aimed to examine the relationship between democratic parenting style and student independence, as well as differences in student independence based on socioeconomic status. This study employed a quantitative approach with a cross-sectional design. Participants were 200 active male and female university students in Indonesia aged 18–25 years. Data were collected using Likert-scale instruments to measure democratic parenting style and student independence, while socioeconomic status was assessed based on family income classification from the Central Statistics Agency o Indonesia. Data were analyzed using Spearman’s rank-order correlation, Kruskal–Wallis test, and Mann–Whitney U test. The results showed a significant positive relationship between democratic parenting style and student independence (ρ=.326, p<.001). Meanwhile, socioeconomic status did not show significant differences in student independence across groups (p=.990). These findings suggest that democratic parenting style is associated with higher levels of student independence, whereas socioeconomic conditions alone may not sufficiently explain variations in student independence. The findings highlight the importance of improving parenting quality through democratic parenting practices, including open communication, emotional support, and providing opportunities for children to participate in decision-making processes.